Spooling diameter dependent Q-switched output in depressed cladding erbium doped laser with MoWS2 saturable absorber - Ahmad, Harith; Reduan, Siti Aisyah (Elsevier, 2018)
A tunable, Q-switched depressed-cladding erbium-doped fiber (DC-EDF) laser employing a molybdenum tungsten disulfide (MoWS2) thin film as a saturable absorber (SA) is reported. The output of the laser can be controlled by adjusting the spooling diameter of the gain medium, with continuous wave operation obtained from 1466 nm to 1502 nm and 1473 nm to 1525 nm for DC-EDF spooling diameters of 5.5 cm and 6.5 cm respectively. The Q-switched output, obtained by incorporating an MoWS2 based SA into the cavity shortens the tuning range to between 1476.0 nm and 1496.0 nm as well as 1486.0 to 1496.0 nm for the same spooling diameters. The outputs have repetition rates ranging from 21.7 kHz to 44.6 kHz and a minimum pulse width and maximum pulse energy of 2.4 µs and 11.0 nJ, for the DC-EDF with a spooling diameter of 5.5 cm. The DC EDF with a spooling diameter of 6.5 cm is able to generate pulses with a repetition rate of between 32.2 kHz and 40.9 kHz with a minimum pulse width and maximum pulse energy of 2.8 µs and 10.1 nJ.